A dual "Turn-on/Turn-off" "FRET" sensor for highly sensitive and selective detection of lead and methylene blue based on fluorescent dansyl tagged copolymer and small molecule diketopyrrolopyrrole. (October 2019) - Chini, Mrinmoy Kumar; Kumar, Vishal; Maiti, Binoy; De, Priyadarsi; Satapathi, Soumitra
Abstract: Here we report, a multimodal sensing platform for sensitive and selective detection of heavy metal Lead (Pb +2 ) and organic dye (Methylene Blue) employing a novel FRET pair between a fluorescent polymer and a small molecule. The FRET pair consists of the highly fluorescent dansyl tagged copolymer P(MMA -co- Dansyl-Ala-HEMA) (DCP ) and small molecule diketopyrrolopyrrole (DPP ). The overlap integral of the FRET pair is calculated to be 1.14 × 10 16 nm 4 /(M*cm) and energy transfer efficiency is determined to be 25%. The fluorescence intensity of the studied FRET pair has been found to be quenched ("Turn Off") and enhanced ("Turn On") in the presence of methylene blue (MB) and lead (Pb +2 ) respectively. The FRET pair shows a strong affinity for Pb +2 ions with very low detection limit (LOD) (27.8 ppm). High KSV (3.9 × 10 4  M −1 ) for MB sensing with LOD value 295 ppb indicates enhanced photo-induced electron transfer from FRET pair to MB. The metal-induced modulation of the self-assembled polymer-small molecule-Pb complex in the solution lead to the photoluminescence enhancement in the presence of Pb +2 and the dynamic quenching is established as the fluorescence Turn-off mechanism in the presence of MB dye. Our multimodal FRET sensing probe offer a common platform for the selective detection of a broad range of toxic pollutants which opens up its possibility of use in field applications. Graphical abstract: Image 1 Highlights: The highly fluorescent dansyl tagged copolymer P(MMA-co-Dansyl-Ala-HEMA) (DCP ) and diketopyrrolopyrrole (DPP ) derivative based FRET sensing system are designed and characterized in details. The fluorescence intensity of the studied FRET pair has been found to be quenched ("Turn Off") and enhanced ("Turn On") in the presence of methylene blue (MB) and lead (Pb +2 ) respectively. Designed FRET pair shows a strong affinity for Pb +2 ions and high Stern Volmer constant for MB sensing with a significant lower LOD. Our multimodal FRET sensing probe offer a common platform for the selective detection of a broad range of toxic pollutants which opens up its possibility of use in field applications.